The p24 proteins are not essential for vesicular transport in Saccharomyces cerevisiae - Springer, Sebastian (The National Academy of Sciences, 2000)
To investigate the factors involved in the sorting of cargo proteins into COPII endoplasmic reticulum (ER) to Golgi apparatus transport vesicles, we have created a strain of S. cerevisiae (p24Δ8) that lacks all eight members of the p24 family of transmembrane proteins (Emp24p, Erv25p, and Erp1p to Erp6p). The p24 proteins have been implicated in COPI and COPII vesicle formation, cargo protein sorting, and regulation of vesicular transport in eukaryotic cells. We find that p24Δ8 cells grow identically to wild type and show delays of invertase and Gas1p ER-to-Golgi transport identical to those seen in a single Δemp24 deletion strain. Thus, p24 proteins do not have an essential function in the secretory pathway. Instead, they may serve as quality control factors to restrict the entry of proteins into COPII vesicles.